Effect of different quenching methods on Pb substituted "2212" bismuth superconductor - K. Eaiprasertsak (2018)
The effects of quenching the lead doped bismuth superconductor Bi 3.3 Pb 0.7 Sr 4 Ca 2 Cu 4 O 16 from 845 K in liquid nitrogen and in flowing argon gas atmosphere are studied. For both types of quenching, the resulting superconductors are multiphase ones as can be seen from their XRD patterns. The T c 's of the LN 2 quenched samples are slightly higher than the T c of the argon gas quenched samples, 90-91 K versus 89 K. Prolonged heating prior to quenching appears to reduce the volume fraction of the high temperature phase in the liquid nitrogen quenched samples. The extrapolated zero resistivity temperature of the high temperature phase is in the range 104-108 K. © 1989.